From Inca province to repartimiento:: Tarapaca in the XVth and XVIth centuries (South Central Andes) - Urbina, Simon; Uribe, Mauricio; Agüero, Carolina; Zori, Colleen (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2019)
The Inca Empire reorganized conquered populations in different jurisdictions imposing the decimal system over local chieftainships or curacazgos, creating new provinces or administrative units where the local authorities lost, maintained or amplified their regional power. The system of encomiendas implemented by early Hispanic conquerors instrumentalized the indigenous political organization active in Inca times as a strategy to maintain the cohesion of the social units (tributaries) that supported the economy in each repartimiento and the payment of taxes that curacas had to give annually to the encomendero. The ethnohistorical study of Tarapaca (Lat. S 19º-21º) allows us to point out crucial aspects related to Inca expansionary policy in this territory, the manipulation of inherited political structures by the Spaniards, the organization of its populations, settlements and authorities, as well as the economic structure regional in the 15th and 16th centuries, demonstrating the originality of some old research hypotheses and the degree of convergence and uniqueness of the political history of this region in the context of the South Central Andes.